2012
DOI: 10.1111/j.1365-2044.2012.07073.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short time periods of pre‐operative warming in the prevention of peri‐operative hypothermia

Abstract: SummaryThe aim of our study was to evaluate the performance of different durations of active pre-operative skin-surface warming (pre-warming) to prevent peri-operative hypothermia and postoperative shivering. We randomly assigned 200 patients, scheduled for surgery of 30-90 min under general anaesthesia, to receive passive insulation or forced-air skin surface warming for 10, 20 or 30 min. Body temperature was measured at the tympanic membrane. Shivering was graded by visual inspection. There were significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
2
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 17 publications
4
116
2
13
Order By: Relevance
“…Although some experiments have 13 (52) 12 ( revealed that 30 minutes of prewarming is needed to gain heat content exceeding the amount of redistribution [14], another study has shown that prewarming for 20 minutes can reduce the risk of perioperative hypothermia [18]. Jo et al [19] have conducted controlled trial and found that prewarming for 20 minutes cannot reduce the incidence of intraoperative hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Although some experiments have 13 (52) 12 ( revealed that 30 minutes of prewarming is needed to gain heat content exceeding the amount of redistribution [14], another study has shown that prewarming for 20 minutes can reduce the risk of perioperative hypothermia [18]. Jo et al [19] have conducted controlled trial and found that prewarming for 20 minutes cannot reduce the incidence of intraoperative hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Prewarming before induction of anaesthesia is the only technique that has been shown to attenuate redistributive heat loss. The maximal effect takes 2 h to achieve [100], although periods as short as 10 min have a significant effect [101]. The optimal combination of practicality and effectiveness has yet to be determined.…”
Section: Resistive Heatingmentioning
confidence: 99%
“…This strategy has been shown to significantly attenuate, and prevent, hypothermia from redistribution of blood from the patient's core to periphery while under general anesthesia [71][72][73][74][75]. Recently, prewarming the patient for as little as 10 to 20 minutes has been shown as effective at reducing perioperative hypothermia and postoperative shivering [75]. Disadvantages with preoperative warming include reduced efficacy with sweating and patient discomfort [72,75].…”
Section: Scip Measurement and Maintenance Of Normothermiamentioning
confidence: 99%
“…Recently, prewarming the patient for as little as 10 to 20 minutes has been shown as effective at reducing perioperative hypothermia and postoperative shivering [75]. Disadvantages with preoperative warming include reduced efficacy with sweating and patient discomfort [72,75]. The Artic Sun™ Temperature Management System (Medivance Inc., Louisville, CO) has been shown "to be more effective for rewarming patients after off-pump coronary artery bypass than conventional warming methods. "…”
Section: Scip Measurement and Maintenance Of Normothermiamentioning
confidence: 99%